Morfofisiologia e exigências térmicas de Cyperus difformis L. (Cyperaceae) - Voss, Higor Modesto Garlet (2018)
The species Cyperus difformis (L.) (tiririquinha) is prominent in the South of Brazil as weed in flooded areas, especially in irrigated paddy rice cultivation under a pre-germinated system. However, in recent years, it has been reported the potential of the species to develop in areas with lower levels of water in the soil, typical of irrigated rice cultivation under a conventional system. In both ecosystems, little is known about its biology and phenology, which often leads to misinterpretations by the technical community as to its characterization and management. The objective of this work was to characterize the morphology and physiological parameters as well as the thermal requirements of Cyperus difformis under different soil water regimes. For that, two experiments were carried out under greenhouse conditions in the year 2016/2017. The first experiment spaced in a mean of 23 days, consisted in the submission of specimens of the species to five soil water conditions: water depth (5 cm), 100% and 50% of the water retention capacity (WRC) of the soil from the sowing, water depth and 50% of soil WRC started at 21 days after emergence. Being characterized the base temperature, thermal sum in degree days (oC) and the duration of the life cycle in the three subperiods determined: sowing-emergence; emergence-issue of floral garlan dand issuing of physiological floral-maturing tassel. The second experiment was carried out in four experimental periods, Were evaluated at 30, 38 and 52 days after emergence (DAE) photosynthetic parameters: photosynthetic rate (A), stomatal conductance (Gs), intercellular CO2 concentration (Ci), transpiration (E), water use efficiency and the rubisco assimilation CO2 ratio (A / Ci), as well as determining morphological parameters at the end of the life cycle. Where the plants of the species were submitted to the same water regimes mentioned in experiment 1. It’s concluded that when subjected to water restriction of 50% of the soil WRC from the beginning, C. difformis is not able to germinate and emerge. When the water restriction started at 21 DAE, the species delays the biological cycle in 12 days, presents morphological results lower than the other water conditions, also presents a lower photosynthetic rate. With presence of water blade, the species was superior in physiological and morphological parameters, resulting in greater accumulation if thermal sum, resulting in the smallest biological cycle. In a saturated soil condition (100% of soil WRC), the species showed intermediate results between the conditions with the presence of water depth and water restriction, characterizing itself as favorable to the development of the weed species.